(untitled) (Research, Society and Development, 2022)
The study aims to assess the importance of sleep in adolescent health. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases, through of the following Health Sciences Descriptors (DeCS): “sleep”, “adolescent health” and “adolescent”. Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not cover the topic and repeated studies in the databases. 68 articles were found, after the combined search of descriptors and Boolean operators, 10 articles were selected to compose the final sample. It is concluded, from all the way with the current project, that these studied and deliberate modifications promote greater sleep aptitude for both the young people involved in the movement and for each person who takes advantage of all the adjustments in nocturnal habits that have been proposed.